2020
DOI: 10.1186/s12884-020-03491-w
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Low birthweight, prematurity, and intrauterine growth restriction: results from the baseline data of the first indigenous birth cohort in Brazil (Guarani Birth Cohort)

Abstract: An amendment to this paper has been published and can be accessed via the original article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
1
0
0
1
Order By: Relevance
“…Prematurity was also found to be related to other factors, such as ethnicity, marital status, maternal age, type of delivery, prenatal appointments, birth weight, and Apgar score, which has already been confirmed in the literature 36 . In this study, we observed that Indigenous people have a higher chance of giving a premature birth, as described by Martinelli et al 36 and Barreto et al 37 . ----------------------------------------------------PM: particulate matter; 95%CI: 95% confidence interval.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Prematurity was also found to be related to other factors, such as ethnicity, marital status, maternal age, type of delivery, prenatal appointments, birth weight, and Apgar score, which has already been confirmed in the literature 36 . In this study, we observed that Indigenous people have a higher chance of giving a premature birth, as described by Martinelli et al 36 and Barreto et al 37 . ----------------------------------------------------PM: particulate matter; 95%CI: 95% confidence interval.…”
Section: Discussionsupporting
confidence: 84%
“…A prematuridade também está relacionada a outros fatores, como raça, estado civil, idade materna, tipo de parto, consulta pré-natal, peso e Apgar, já bem estabelecidos na literatura 36 . Neste estudo, observamos que indígenas têm uma maior chance de prematuridade, assim como descrito por Martinelli et al 36 e Barreto et al 37 …”
Section: Discussionunclassified